Generalized Soft Intersectional Ideals in Ternary Semirings - Mahmood, Tahir; Waqas, Ayesha; Rana, M. A.; Tariq, Usman (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2014)
In this paper we introduce the notions of soft intersectional ternary subsemirings and soft intersectional ideals in ternary semirings. We also discuss some basic results associated with these notions. In the last part of the paper we characterize regular and weakly regular ternary semirings by their soft intersectional ideals.